About the Political Economy in the Department "Political Economy" at UNWE - Toshkova, Svetla (Research Papers, 2017)
The study presents one of the contemporary understandings of political economy in the context of the historical development of economic theory and the changes in the methodology and philosophy of economic knowledge. An attempt has been made to define the objectives, the object and the subject area of ??political economy as an interdisciplinary science in the economic and policy fields with taking into account the influence of institutional, socio-cultural and value factors. At the same time, the thesis of looking for the role and place of political economy and its modern development is defended in the context of the interaction between the different contemporary concepts of political economy, which should not be opposed but viewed as a starting point for the creation of the contemporary concept of political economy and its interactions with other sciences from the broad spectrum of highly integrated contemporary socio-economic knowledge in the era of post-industrial society and the globalized world. The main problem areas in the curriculum for political economy and the content of the curriculum of the specialty are briefly presented.
Keywords: Economic theory; History and methodology; Political economy